ALTERNATION OF HEMATOLOGICAL AND SERUM BIOCHEMICAL PROFILES IN DOGS NATURALLY INFECTED WITH HEPATOZOON CANIS IN SOUTH WESTERN GUJARAT, INDIA - B.R. Maharana; Binod Kumar; B. J. Thakre; N. D. Hirani; T. K. Patbandha (Indian Journal of Veterinary and Animal Sciences Research, 2025)
This study represents Hepatozoon canis infection in three among seventy eight dogs referred  to Teaching Veterinary Clinical Complex  (TVCC),  Veterinary College,  Junagadh from  January to  April 2013 with  prior history of anorexia, anemia, depression and  difficulty in   locomotion.  Significant    clinical    findings    included    higher    body    temperature    (106oF),   enlarged lymph nodes and congested mucus membrane. Blood smears were stained with Giemsa stain  revealed capsule  shaped  gametocytes of H. canis in the  cytoplasm  of approximately 15  to  20% circulating neutrophils. This is the first time documentation  of hepatozoonosis in dogs from south western Gujarat, India and hence placed on record.